The Space of the Artist as Heterotopia: Recontextualization of the Studio Whitin an Educational and Sociocultural Project - Barreiro Rodríguez-Moldes, María Covadonga; Paz García, María Begoña; Ezquieta Llamas, Icíar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Workshop, studio, laboratory, factory... the artist’s work space has been taking several names, assuming different forms and configurations. But in essence it is a functional space where each artist creates and produces their work. It is a highly symbolic, active and performative context, an ideal place for the execution of actions and processes in which to explore the phenomenology of the medium as an educational space. “Artist’s Space” is an artistic-pedagogical project that takes the studio or workshop as a mediator of the artistic experience within the XXII Children’s and Youth Book Fair of Pontevedra.